Long wavelength (λ > 13 μm) quantum cascade laser based on diagonal transition and three-phonon-resonance design - Jin, Yuhao (2021)
An InP-based quantum cascade laser structure emitting at a wavelength of 13.6 μm is proposed and demonstrated. The active region is based on a diagonal transition and three-phonon-resonance design. A 5 mm long, 30 μm wide high-reflection coated device with a double channel ridge waveguide structure has shown a threshold current density of 3.0 kA/cm2, a dynamic range of 4.4 kA/cm2, a peak output power close to 1 W, and an average optical power up to 11.7 mW at 3% duty cycle, at 293 K. The laser shows a characteristic temperature T0 of 314 K and T1 of 336 K over a temperature range from 283 to 313 K.